Iron Metabolism and Ferroptosis in Epilepsy - Chen, Shuang; Chen, Yongmin; Zhang, Yukang; Kuang, Xi; Liu, Yan; Guo, Meiwen; Ma, Lin; Zhang, Daqi; Li, Qifu (Frontiers in Neuroscience, 2020)
Epilepsy is a disease characterized by recurrent, episodic and transient central nervous system (CNS) dysfunction resulting from excessive synchronous discharge of brain neurons. It has the characteristics of diverse etiology, complex pathogenesis and difficult treatment. Meanwhile, most epileptic patients have social cognitive impairment and psychological impairment. Iron is an essential trace element for human growth and development. Iron compounds are also involved in a variety of redox reactions in organisms. However, abnormal iron metabolism is associated with a variety of neurological disorders, including hemorrhagic post-stroke epilepsy and post-traumatic epilepsy (PTE). Meanwhile, ferroptosis is also considered to be a new form of regulation of cell death, which attributes to severe lipid peroxidation caused by the production of reactive oxygen species (ROS) and iron overload, and it is found in a variety of neurological diseases including epilepsy. Therefore, this review summarizes the research on iron metabolism and ferroptosis in epilepsy, so as to fully understand the relationship between iron and epilepsy. Meanwhile, it also provides a new idea for the treatment, prevention and research of epilepsy, so as to control epileptic seizure more effectively and reduce the nerve injury after epileptic seizure.